Study on the Relationship of Current Stability and Tribological Property in Red Copper/Chromium Bronze Pair - ZHAO Yan - wen, SUN Le - min (Cailiao Baohu, 2021)
Dynamic current collection quality and conductivity stability are very important indexes on evaluating the performance of current carrying by friction pair collector. Taking pure copper and chromium bronze as research objects, the relationship between conductive stability and tribological property of current carrying friction pair at low speed was discussed on a self - made current carrying tester. Results showed that the change trend of conductivity stability and friction coefficient stability of matching pair was consistent and mutual - promotion and mutual - gain. While obtaining current carrying stability, the friction performance was also in a stable state. Both of them tended to be more stable with the increase of current and load. The friction pair not only obtained high and stable dynamic current receiving capacity, but also was in a good state of tribological characteristics, which was conducive to improving wear resistance and reducing wear.